2014
DOI: 10.3390/rs6076688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bias Correction of Satellite-Rainfall Estimates on Runoff Simulations at the Source of the Upper Blue Nile

Abstract: Abstract:Results of numerous evaluation studies indicated that satellite-rainfall products are contaminated with significant systematic and random errors. Therefore, such products may require refinement and correction before being used for hydrologic applications. In the present study, we explore a rainfall-runoff modeling application using the Climate Prediction Center-MORPHing (CMORPH) satellite rainfall product. The study area is the Gilgel Abbay catchment situated at the source basin of the Upper Blue Nile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 53 publications
5
108
0
Order By: Relevance
“…For ungauged areas, however, use of multisource SREs would be another possibility of the bias correction, and monthly-and seasonal-basis scale factors can also be employed for the bias adjustment. There have been several studies to apply and evaluate some advanced methods which enable bias correction of SREs, even in sparsely gauged areas [37,38]. At the same time, dependence of SREs on topography, season, and other factors are being studied for bias correction [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…For ungauged areas, however, use of multisource SREs would be another possibility of the bias correction, and monthly-and seasonal-basis scale factors can also be employed for the bias adjustment. There have been several studies to apply and evaluate some advanced methods which enable bias correction of SREs, even in sparsely gauged areas [37,38]. At the same time, dependence of SREs on topography, season, and other factors are being studied for bias correction [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The consistent under prediction could be easily bias corrected with a linear bias correction [26]. While maximum temperature did not show a consistent bias, in this case, bias could be corrected with histogram matching, gamma or power transformation functions among others [48,[58][59][60].…”
Section: Downscaled Precipitation Maximum and Minimum Temperature Fomentioning
confidence: 99%
“…Among the two approaches, Artan et al (2007) and Zeweldi et al (2011) indicated that performance of a hydrological model when the model was calibrated using gridded rainfall data is better than this when it was calibrated using rain gauges data. However, calibration could result in parameter values that are unrealistic as the model attempt to compensate for the large errors in rainfall input (Habib et al, 2014). Thus, the first approach was used in this study.…”
Section: Trmm Datasetmentioning
confidence: 99%